AB1070 Unravelling autoimmune diseases through nailfold capillaroscopy. (15th June 2017) - Bernardino, VR; Rodrigues, AC; Llado, AC; Fernandes, MA; Vicente, M; Grilo, AC; Panarra, A; Moraes-Fontes, MF
Abstract : Background: Nailfold capillaroscopy (NC) is non-invasive and used by clinicians as a diagnostic tool. It allows the distinction between primary and secondary Raynaud Phenomenon (RP), the latter usually associated to autoimmune diseases (AID). Objectives: Characterize the utility of NC assessment for diagnosis of AID and to evaluate main differences in NC pattern, according to the presence of RP. Methods: NC were performed with a Videocap biomicroscope using well established classification criteria [1]. NC images and reports from all patients evaluated from January 2011 to final December 2016 were retrospectively analysed. Comparisons were made using the Wilcoxon Rank Sum and Chi square tests, p values of <0, 05 were considered statistically significant. Results: In the last 6 years, 1100 NC were performed, 159 to man and 941 to women. Mean age was 42 [±19] years. NC requests came from 17 different hospital units. RP was present in 83% of patients (RP+, n=909) of whom 71% (n=641) had a prior diagnosis of AID, most frequently Systemic Sclerosis (SSc) (24%, n=143), Systemic Lupus Erythematosus (SLE) (21%, n=123), Sjögren's Syndrome (SS) (10%, n=62), Mixed Connective Tissue Disease (MCTD) (9%, n=52) and Antiphospholipid Syndrome (APS) (8%, n=48). NC patterns allowed for the classification of RP+ subjects into primary (3%) and secondary (81%); in 4% of subjects NC findings were abnormal but inconclusive. From secondary RP, scleroderma (37%) and non-scleroderma pattern (62%) were further separated; the former was later classified according to scleroderma-like (15, 02%), early (33%), active (38%) and late (15%) scleroderma patterns.29% of RP+ patients did not have AID diagnosed; NC disclosed the diagnosis of SSc (n=24), APS (n=5), SS (n=4), SLE (n=2), MCTD (n=1), overlapping syndrome (n=1) and paraneoplastic syndrome (n=1). In RP- patients, the main diagnosed AID were SLE (20%, n=17), SSc (14%, n=12) and SS (8%, n=7). NC results in RP- subjects were normal (24%) (including 92% of controls), inconclusive (22%) and suggestive of capillaritis (16%). Although RP-, some patients (38%) presented dysmorphic capillaries suggestive of secondary involvement (38%); NC findings in these patients included megacapillaries and microhemorrhages (scleroderma-like (26%), early (41%), active (30%) and late (7%)). Demographic data was similar in both groups. Statistically significantly higher frequencies of AID (p<0.0001), SSc (p=0.0006), NC secondary non-SSc pattern (p<0.0001) and NC secondary active SSc pattern (p=0.002) were found in RP+ patients. Conclusions: NC findings in RP+ were more pathological than in RP-subjects, probably due to pre-existing AID and more frequent positivity. Secondary non scleroderma pattern was more prevalent in RP+ patients. In RP- group, almost a quarter of NC assessments were normal, but capillary abnormalities were also revealed, suggesting this diagnostic approach can help to disclosure microvascular disease, even if RP is absent. NC further disclosed important leads to diagnose SSc, APS and MCTD in our population. References: Cutolo M et al. Arthritis and Rheumatism. 2003 Nov; 48(11):3023–3030. Disclosure of Interest: None declared